A case study of tertiary learners’ capability in lexical knowledge - Naginder Kaur (Penerbit UKM, 2013)
Lexical competence is crucial in ensuring academic success at all levels. At tertiary level, sufficient word knowledge and lexical comprehension ensure sufficient literacy of language skills as learners need to cope with challenging academic tasks in their respective field of study. This paper reports findings of a case study of pre-degree Malaysian learners enrolled at Universiti Teknologi MARA (UiTM) Perlis. The study was undertaken to find out if these learners have sufficient lexical ability before they embark on a degree programme. Nine learners of varying proficiency levels of high, average and low language proficiency were selected for this study. The data were collected in sequential two-phased procedure. The first phase involved diagnostic stage of probing learners’ level of word knowledge with online Vocabulary Levels Test by Laufer and Nation. Subsequently, learners’ capability within the scope of word form, spelling and pronunciation was explored through the Academic Word List Test and in-depth interviews with the participants. The findings revealed that the learners’ word mastery level is only between 1,000 and 3,000 words, which is far below the minimum level required for tertiary education. These insights thus inform the researcher that urgent measures must be taken in order to redeem the situation. Hence, a structured vocabulary learning programme is deemed necessary in the Malaysian English language curriculum to help learners acquire sufficient lexis before embarking on tertiary education. This would also provide our tertiary learners with the avenue to make them employable and marketable graduates with firm language proficiency in general and lexical competence in particular.